Akseptabilitas dan Pemanfaatan Pusat Informasi dan Konsultasi Kesehatan Reproduksi Remaja pada Siswa Sekolah Menengah Umum - Arie Afrima Djauhar Ismail Ova Emilia (Fakultas Kedokteran Universitas Gadjah Mada, 2011)
Background: Adolescent period is a transition period from childhood to adulthood. One sixth of people on earth are adolescents and 85% of them live in developing countries. Adolescents often encounter risks of reproductive health so that reproductive health service becomes necessary for adolescents. School is a center of the dissemination of reproductive health information. The problem is that PIK-KRR in schools is underutilized. Factors causing underutilization are access to service, needs of adolescents, and acceptability of students to PIK-KRR.Objectives: To study the relationship between acceptability to PIK-KRR and utilization to PIK-KRR in schools by senior high school students at Bima Municipality Nusa Tenggara Barat.Method: The study used cross sectional with quantitative as well as qualitative approaches. Subjects were 312 high school students. Data were obtained through questionnaire and in-depth interview and analyzed using univariate, bivariate with chi-square and multivariate with logistic regression.Result: The result of bivariate analysis showed there was significant association between utilization and acceptability, need and attitude toward reproductive health (p<0.05). The result of multivariate analysis showed there was significant association between the utilization and acceptability (RP=1.5; CI95%=1.21-1.91). There was significant association between the utilization and acceptability after the control of variable of need (RP=1.4; CI95%=1.18-1.85) and with the control of variable of attitude consistently there was significant association between the utilization and acceptability (RP=1.4; CI95%=1.11-1.95). This mean that students accepting PIK-KRR had positive attitude toward reproductive health than those not accepting PIK-KRR.Conclusion: The utilization of PIK-KRR in school was associated with acceptability, need and attitude toward reproductive health.Keywords: acceptability, reproductive health, utilization, adolescents